The News Types of Two Countries: A Comparative Study of News Values Quality Newspapers and Popular Newspapers in Malaysian and Britain - Othman, Siti Suriani; Tiung, Lee Kuok (SOSIOHUMANIKA, 2009)
ABSTRACT: This study examined the news values in the front page lead stories and thus identified types of news that frequently published in front pages of two quality newspapers and two primary tabloid newspapers from Malaysia and Britain. Sample for this research taken from March 2008 and content analysis had been used as the research method for the further development of this research. This comparative study is not merely assessing the distinction or similarity within these quality and popular newspapers in Malaysia and Britain, but also to compare the different newspaper format used in both selected countries. The findings indicating that quality newspaper from both countries are prone to report news regarding on politics, economics, and internal issues involved in the country itself. The worthiness or the values of this news consist of traits such as magnitude, surprise, bad news, and the power elite. In contrast of popular newspapers, it emphasize heavily on sensational news such as crime news stories, social illness, and so forth where these news items gripping strongly on traits such as entertainment, surprise news, bad news, and celebrity news. Key words: news values, quality newspapers, popular newspapers, comparative study, and Malaysia and Great Britain news papers.Â Â Â About the Authors: Siti Suriani Othman is a Lecturer at the Malaysia University of Islamic Science (USIM), Seremban, Negeri Sembilan, Malaysia; and Lee Kuok Tiung is a Lecturer at the Malaysia University of Sabah (UMS), Kota Kinabalu, Sabah, Malaysia. For academic purposes, they can be reached at: suriani@usim.edu.my or suria3979@gmail.com; and lee@ums.edu.my or leekuoktiung@hotmail.com Â How to cite this article? Othman, Siti Suriani & Lee Kuok Tiung. (2009). âThe News Types of Two Countries: A Comparative Study of News Values Quality Newspapers and Popular Newspapers in Malaysian and Britainâ in SOSIOHUMANIKA: Jurnal Pendidikan Sains Sosial dan Kemanusiaan, Vol.2, No.2 [November], pp.197-214. Bandung, Indonesia: Minda Masagi Press, UNIPA Surabaya, and UMS Kota Kinabalu, Malaysia, ISSN 1979-0112. Chronicle of article: Accepted (September 20, 2009); Revised (October 24, 2009); and Published (November 20, 2009). Â Â